Lateral throat form classification using a customized gauge and Neil’s method – a comparative study - Poudel, Sabina; Dhungana, Minu; Karki, Rajani; Shrestha, Prabhat (Journal of Chitwan Medical College, 2018)
Introduction: Lateral throat form (LTF) is the critical area which has to be recorded properly for obtaining proper retention and stability in complete denture especially in geriatric patients with resorbed ridges. Popular method used for determining LTF is Neil’s method which depends on the forces applied by the floor of mouth when the tongues protrude out. Since the perception of the forces differs among different operators, there are high chances of error in the classification. So, customized instrument was fabricated to prevent this inter-observer variation. The aim of the study was to compare the inter-observer accuracy between Neil’s method of classification and classification done by customized gauze. Methods and methodology: Total 30 edentulous patients were taken. Two observers measured the LTF depth by customized tool and also by Neil’s method. Cohen’s kappa test was used to evaluate the agreement between two operators in two different classifications. Result: The agreement between the two observers was evaluated by means of Cohen’s kappa value. There was good agreement between observers in proposed classification done by customized tool with kappa value 0.658 and fair inter-observer agreement with kappa value 0.0492. Conclusion: The method of measuring the depth of LTF with fabricated instrument was more accurate and reliable than Neil’s method.